Management of Locally Recurrent Chordoma of the Mobile Spine and Sacrum: A Systematic Review. (15th October 2016) - Ailon, Tamir; Torabi, Radmehr; Fisher, Charles G.; Rhines, Laurence D.; Clarke, Michelle J.; Bettegowda, Chetan; Boriani, Stefano; Yamada, Yoshiya J.; Kawahara, Norio; Varga, Peter P.; Shin, John H.; Saghal, Arjun; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Systematic review. Objective: To determine evidence-based guidelines for the management of locally recurrent spinal chordoma. Summary of Background Data: Chordoma of the spine is a low-grade malignant tumor with a strong propensity for local recurrence. Salvage therapy is challenging due to its relentless nature and refractoriness to adjuvant therapies. There are currently no guidelines regarding the best management of recurrent chordoma. Methods: We combined the results of a systematic review with expert opinion to address the following research questions: (1) For locally recurrent chordoma of the spine without systemic disease, if surgery is planned, should en bloc resection be attempted if technically feasible with acceptable morbidity? (2) For locally recurrent chordoma without systemic disease, in which wide en bloc excision is not possible, what is the treatment of choice? (2) Should adjuvant or neoadjuvant radiation therapy be used in the treatment of locally recurrent chordoma? Results: A total of nine surgical and seven radiation therapy articles met study criteria. Evidence quality was low or very low. Recurrent disease is associated with predominantly poor outcome, regardless of treatment modality. As for primary chordoma, resection with wide margins appears to confer an advantage with respect to local control, although this effect is attenuated in the setting of relapse. Postoperative radiation therapy likely reduces the rate of further relapse. Conclusion: (1) For locally recurrent chordoma of the spine without systemic disease, when surgery is planned, wide en bloc resection should be performed if technically feasible with acceptable morbidity. Strong recommendation, Low Quality of Evidence. (2) For locally recurrent chordoma without systemic disease, in which wide en bloc excision is not possible, partial resection is the treatment of choice. Weak recommendation, Very Low Quality of Evidence. (3) For the treatment of locally recurrent chordoma, high-dose conformal radiation therapy should be administered postoperatively to reduce the risk of further recurrence, and may be considered as a primary therapy. Strong recommendation, Very Low Quality of Evidence. Level of Evidence : 2